Analysis of Total, Direct and Indirect Cost Outliers in a Polish Specialist Hospital - Cygańska, Małgorzata; Thoene, Michael; Silva, Amelia (Olsztyn Economic Journal, 2017)
The purpose of this study is to analyze the factors facilitating the identification of the three categories of cost outliers. They are known as total cost outliers (TCO), direct cost outliers (DCO), and indirect cost outliers (ICO). 4,570 patients have been analyzed. To evaluate the factors that influence the patient being a cost outlier in a hospital; age, length of stay, gender, type of admission, reason for discharge, and type of department were considered. Multivariable logistic regression was used in the study. In our research TCO comprised 9% of the study sample. The percentage of DCO was slightly higher (10%) and ICO was slightly lower (8%). Total cost outliers accounted for almost 37% of total hospital costs, 40% of direct costs, and 34% of indirect costs. The direct cost outliers accounted for 44.39% of direct costs, and indirect cost outliers accounted for 34.91% of indirect costs. It was discovered that, in terms of gender, men are positively correlated with higher cost utilization. The risk of being a cost outlier increases risk in terms of death and referral for further treatment. The type of admission factor can only be a predictor of being an ICO. The risk of a patient being a length of stay outlier increases far more for the ICO (more than 580 times) than in the case of a DCO (3.81 times) or a TCO (13.79 times). The analysis suggests that not only TCO, but also DCO and ICO, should have high priority for hospital managers concerned with variations in the costs of care.